User Flow Design Research for a Culinary Application Prototype to Improve Customer Satisfaction in Balikpapan - Luh Made Wisnu Satyaninggrat; Khairunnisa Rahmah; Prasis Damai Nursyam Hamijaya (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Balikpapan's economic growth is predicted to rise to 4.94% in 2022 from 4.56% in 2021. The Business Field for Providing Accommodation and Food and Drink has performed well, helping the city's economy. In Balikpapan, 23% of the creative economy is in the culinary sector. Culinary tourism is popular in the city, although finding gastronomic information, especially for foreigners, can be difficult. As a result, there is a need for a culinary application that can provide information about Balikpapan's different culinary delights. Prior to developing a culinary application, the initial step entails the creation of a user flow. This user flow aims to establish a development team for the purpose of creating culinary apps that align with user requirements and customer satisfaction. The process of developing a user flow encompasses multiple steps, including literature research, understanding context of use, specify user requirements, and design user flow solution.  Several elements and processes that can be included in a culinary application have been identified through research conducted with 30 entrepreneurs and 30 food enthusiasts. Ratings, delivery services, promotions, menus, favorite menus, best seller menus, payment options, order services, training, reports, maps, and other features are available. By displaying the user flow and offering step-by-step instructions for users, this research serves as the first stage in constructing the culinary application. The user flow will aid in communication and demonstrating how the culinary application functions. The findings will also be used to develop a culinary application prototype that demonstrates the user interface and user experience.